JBIR-150, a novel 20-membered polyene macrolactam from marine-derived Streptomyces sp. OPMA00071. (March 2018) - Kawahara, Teppei; Fujiwara, Takeshi; Kagaya, Noritaka; Shin-ya, Kazuo
Abstract During the course of constructing a natural product library for drug screening consisting of microbial culture extracts originated from marine samples, we evaluated natural product components profiles via UPLC TOF-MS and routine biological tests for cytotoxic and antibiotic activities for all of the culture extract samples. By combination of chemical screening and biological activities, we succeeded in discovering a 20-membered macrolactam antibiotic subsequently designated JBIR-150 (1 ) from a marine-derived actinomycete identified asStreptomyces sp. that was isolated from an Okinawan marine sediment. The chemical structure of1 was determined by interpreting NMR spectroscopic and mass spectrometric data. Compound1 exhibited moderate cytotoxicity against MESO-1 and Jurkat cells.